2012
DOI: 10.1038/gt.2011.207
|View full text |Cite
|
Sign up to set email alerts
|

AAV-based shRNA silencing of NF-κB ameliorates muscle pathologies in mdx mice

Abstract: Chronic inflammation, promoted by an upregulated NF-kappa B (NF-kB) pathway, has a key role in Duchenne muscular dystrophy (DMD) patients' pathogenesis. Blocking the NF-kB pathway has been shown to be a viable approach to diminish chronic inflammation and necrosis in the dystrophin-defective mdx mouse, a murine DMD model. In this study, we used the recombinant adeno-associated virus serotype 9 (AAV9) carrying an short hairpin RNA (shRNA) specifically targeting the messenger RNA of NF-kB/p65 (p65-shRNA), the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 35 publications
0
30
0
1
Order By: Relevance
“…Histological analysis was carried out by hematoxylin and eosin staining (H&E), as described previously. 46 …”
Section: Methodsmentioning
confidence: 99%
“…Histological analysis was carried out by hematoxylin and eosin staining (H&E), as described previously. 46 …”
Section: Methodsmentioning
confidence: 99%
“…A recent study has also shown that inhibition of NF-κB improves the proliferation, differentiation, and transplantation of muscle-derived stem cells in dystrophic muscle (Lu et al, 2012). Furthermore, shRNA-mediated knockdown of RelA or overexpression of a dominant negative mutant of IKKα or IKKβ using adeno-associated virus (AAV) also ameliorated pathology and improved regeneration in mdx mice (Tang et al, 2010; Yang et al, 2012). Importantly, specific depletion of IKKβ in macrophages also considerably reduced the expression of inflammatory cytokines, muscle pathology, and enhanced myofiber regeneration (Acharyya et al, 2007) further suggesting that macrophages play an important role in DMD pathology possibly through increased production of NF-κB-regulated proinflammatory cytokines in skeletal muscle microenvironment.…”
Section: Nf-κb Signalingmentioning
confidence: 99%
“…Duchenne muscular dystrophy (DMD) is the most common of the muscular dystrophies and is caused by mutations in the dystrophin gene . The purpose of this article is to highlight the current knowledge and advancements in the evolving paradigms in clinical pharmacology and therapeutics for this devastating musculoskeletal disease.…”
Section: Paradigm Shiftsmentioning
confidence: 99%